Influência do material da ferramenta de corte sobre a usinabilidade do aço ABNT 4340 no torneamento - Bárbara Cristina Mendanha Reis (2017)
Conventional machining is based on the removal of material by means of a cutting tool, which necessarily must have higher hardness and strength relative to the workpiece material. However, due to the constant development of new alloys with higher hardness and mechanical properties, there is a continuing need for new materials for cutting tools, with properties that can overcome the requirements of these alloys. In order to understand the intrinsic phenomena that the variation of theinput parameters (cutting speed, feed rate, cutting tool material and chip breaker) causes the output parameters (cutting force, roughness, chip, cutting temperature and wear tool) turning tests were performed using AISI 4340 steel as waste material experimental. Initially, a full factorial design 2³ was used for statistical analysis together additional tests,thus resulting in 40 tests. Regarding the analysis of cutting force, tool material and feed rate affect significantly the cutting force, with the lowest value achieved with the is concerned cermet and the lowest level of feed rate.Regarding roughness, feed rate was shown as the only influential parameter and the cutting tool material, regardless of the form of chip breaker, did not bring significant benefits. The analysis of chip form showed that higher levels feed produced short chips and that tool material proved to be influential on the form of the chip. As far as the cutting temperature, the results indicated that cemented carbide, LP chip breaker and lower cutting speed levels ensured the lowest cutting temperatures. Finally, for the selected established cutting parameters and length cut it was not possible to identify wear on the cutting tools